ON ENGINEERING ENERGY EFFICIENT INTENSIVE CHEMICAL-TECHNOLOGICAL SYSTEMS IN THE DIGITAL ECONOMY - Yusupov , Lazizjon (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In the context of the digital economy, one of the main intellectual factors for the successful implementation of the socio-economic and environmental goals of sustainable human development, proclaimed by the UN General Assembly in 2000, is the scientific principles and methods of engineering energy-efficient, intensive, environmentally friendly complex chemical-technological systems suitable for the production of chemical complexes and petrochemical complexes. In accordance with the goals of sustainable development, in the context of the digital economy, intensive chemical engineering processes and energy-efficient, environmentally friendly, digitized, complex chemical engineering processes successfully solve the following main organizational, technological and socio-economic tasks in the real sector of the economy: rational use of natural resources; minimizing man-made emissions, including greenhouse gas emissions; protecting the environment from pollution; preserving the biodiversity of natural systems; socio-cultural harmonization of society; increasing the economic efficiency of industrial enterprises and supply chains; improving the quality of life and increasing life expectancy.